Multi-scale study of RTM process modelling in the manufacturing of aerospace composites - Zhao, Xiantao (2018)
Resin Transfer Moulding (RTM) is an advanced manufacturing process for composite components, and is widely applied in industries such as aerospace. A full resin impregnation during RTM is essential to obtain a high-quality component with reduced defects content. To reduce the level of experimental work as well as the cost for optimizing processing parameters, numerical simulation tools are widely used nowadays. The work presented in this thesis is based on one work package from a company sponsored project, focused mainly on research in permeability characterisation and defects generation during the RTM process. From another point of view, this research can be considered as a multi-scale study of RTM process modelling, which consists of a micro-scale study of the fluid-porous interface to determine fibre tow boundary conditions for permeability modelling, a meso-scale study of textiles permeability based on unit cell modelling, and a macro-scale study of RTM process modelling to characterize void formation. Furthermore, experimental work is also included for validation against simulation results. As a key input for RTM process modelling, permeability prediction based on meso-scale unit cell is studied in this research. Micro-CT technology is employed to characterize the internal geometry of 3D woven fabric, which is the input for the generation of unit cell. Besides, geometrical variability is studied for its influence on the permeability prediction results, Due to the dual flow characteristic within 3D woven fabric, proper fibre yarn boundary conditions are developed for permeability modelling with unit cell. Fibre yarn with random fibre distribution models are generated. Flow transverse with the fibre yarn is studied and it’s found that no-slip boundary condition can be applied in the present research. Considering the geometric variability inherent with fabrics, permeability variability study is also conducted in this research. The geometric variability characterization methods are introduced and based on that, the influence of geometric variability on the permeability prediction is studied. Regarding with macro-scale RTM process modelling, parametric study of injection conditions are conducted to investigate its effect on voids formation. Furthermore, permeability experiment of 3D woven fabrics with different fibre volume fraction, as well as parametric study of RTM experiments for voids formation are also included in this research. Comparison of permeability measurement value and modelling results are made, with which the unit cell model is optimized.